2014
DOI: 10.1038/leu.2014.293
|View full text |Cite
|
Sign up to set email alerts
|

The role of TLR8 signaling in acute myeloid leukemia differentiation

Abstract: Acute myeloid leukemia (AML) is an aggressive disease with a poor 5-year survival of 21% that is characterized by a differentiation arrest of immature myeloid cells. For a rare subtype of AML (acute promyeloctyic leukemia, 5-10% of cases) all-trans retinoic acid therapy removes the differentiation block, yielding over a 90% cure rate. However, this treatment is not effective for the other 90-95% of AML patients, suggesting new differentiation strategies are needed. Interestingly, differentiation is induced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 36 publications
7
50
0
2
Order By: Relevance
“…Meanwhile, there was no statistically significant difference between these two groups regarding the level of TLR-9/GAPDH mRNA expression. Our findings were similar to those of previous studies [8,20,21] which evaluated the quantitative expression of TLRs in patients with newly diagnosed or relapsed AML and concluded that the highest level of TLR expression was seen for TLR-7 while there was no significant difference in the expression of the other TLRs compared to the healthy volunteers. Similarly, other studies [6,22,23] demonstrated that the level of TLR-7/β-actin mRNA expression was significantly elevated in AML patients compared to normal cases (P < 0.05).…”
Section: Discussionsupporting
confidence: 81%
“…Meanwhile, there was no statistically significant difference between these two groups regarding the level of TLR-9/GAPDH mRNA expression. Our findings were similar to those of previous studies [8,20,21] which evaluated the quantitative expression of TLRs in patients with newly diagnosed or relapsed AML and concluded that the highest level of TLR expression was seen for TLR-7 while there was no significant difference in the expression of the other TLRs compared to the healthy volunteers. Similarly, other studies [6,22,23] demonstrated that the level of TLR-7/β-actin mRNA expression was significantly elevated in AML patients compared to normal cases (P < 0.05).…”
Section: Discussionsupporting
confidence: 81%
“…To assess the impact of SC1 on in vitro NK cell cytotoxicity, we injected mice with 200 µg SC1 or vehicle solution. Mice were injected with equimolar amounts of R848 (2 mg/kg) and SC1 (2.6 mg/kg), based on the established therapeutic dosage of R848 in murine tumor therapy(31). SC1-treatment significantly increased NK cell mediated target cell lysis at all effector to target cell ratios tested, indicating potent effector cell activation (figure 1D).SC1 induces type 1 interferon and mediates increased NK cell cytotoxicity in vivoSystemic treatment with TLR7 agonists results in cytokine induction, leading to dose limiting systemic adverse effects(13,29).…”
mentioning
confidence: 99%
“…Leukaemia cell differentiation is a key factor to evaluate the malignancy. Previous studies put forward many targets, regulation of which was directly correlated with the leukaemia cell differentiation . On the basis of these reports, our study firstly shows that regulation of HoxA9 expression was able to control the HL‐60 and MOLT‐3 cell differentiation (Figure ).…”
Section: Discussionmentioning
confidence: 59%